Learning Loss Analysis of Introductory Concepts of Chemistry for Students After The COVID-19 Pandemic - Yunita Arian Sani Anwar; I Nyoman Loka; Syarifa Wahidah Al Idrus (Postgraduate, University of Mataram, 2023)
This study analyzes the learning loss of first-year students' chemistry concepts at FKIP, University of Mataram. The research sample was 112 first-year students taking introductory chemistry courses at FKIP University of Mataram, 14 male students (12.5%) and 98 female students (87.5%)—these students, as a whole, face two years of online learning in high school. The primary data in this study is the analysis of respondents' test results related to prior knowledge of chemistry concepts during one semester of lectures. The results showed that the idea of limiting reagents and percent composition showed the highest learning loss (53.57%), while the concept of moles and molar mass and matter showed the lowest learning loss percentage of 32.14%. Furthermore, the results of statistical tests show the relationship between the average score before the UTS implementation and after the UAS implementation. The previous lack of online learning to strengthen students' prior knowledge indicates the cause of learning loss in chemical concepts. Questionnaire analysis stated that education through WA groups, the duration of chemistry learning was low, and the lack of feedback given by teachers on assignments students were working on during the learning process strengthened the current conditions.